How Modern Machinery Replaces Laborers? A Comparative Study of Their Livelihood Before and After Implementation - Dilla, Verline Gaudeene; Dalusong, Reginald Ludwig; Elacion , Lesley Jane; Mina, Franz Cedrick; Vasquez, Roxzyleen Andreih; Villarama, Joseph (Journal of Interdisciplinary Perspectives, 2024)
With modernization, the agricultural sector has increasingly adopted modern machinery, raising concerns about its impact on farm laborers, whose roles are being supplanted by these advanced technologies. This study examined the effects of mechanization on the livelihood of farmers in the Science City of Muñoz, Nueva Ecija, Philippines. Employing a phenomenological qualitative approach and convenience sampling, the research focused on five Filipino farmers who participated in in-depth, semi-structured interviews using a validated, researcher-developed interview guide. Data were analyzed using Colaizzi’s 7-Step Method. The findings reveal that the prevalence of modern machines has significantly contributed to unemployment and financial hardship among farm laborers, posing challenges to their livelihoods. Additionally, the farmers highlighted the importance of education in the agricultural sector and the erosion of the "bayanihan spirit" (communal unity) due to the introduction of modern machinery. This study underscores the dual-edged nature of mechanization: while enhancing efficiency, it also inflicts substantial socio-economic costs on farm workers. Consequently, it calls for a deeper understanding and proactive measures to address the adverse effects on laborers affected by agricultural mechanization.